The Use of LKPD Based on the Make A Match Model to Improve Digital Writing Skills in Low Grade Elementary Schools - Prayitno, Harun Joko; Mahmudah, Siti Nur; Pradana, Fajar Gemilang; Al-Kubro, Putri Balqis; Baihaqi, Muhamad Adzib (International Conference on Education for All, 2024)
This study aims to explain the improvement of digital writing skills by using LKPD based on the make a match model. This research was conducted at SD N Pajang 03, precisely in the lower grade. This research method is descriptive qualitative, with literature study. The data obtained came from primary data and secondary data. Primary data was obtained from direct observation by researchers. Meanwhile, secondary data comes from books, articles, and other written works. There are three ways in data collection techniques, namely, observation, interviews, and documentation. The data analysis technique in this study uses the Miles and Huberman model, namely 1) Data collection; 2) data reduction; 3) data display / data presentation; and 4) drawing conclusions. Testing the validity of the data, researchers used data tringulation techniques, namely by combining the data obtained and reinforced with theories from the results of literature studies or other related research. The results of this study indicate that digital writing skills through LKPD based on the make a match model in low-grade elementary school students are stated to increase, this is evidenced by an increase in digital writing skills between cycle 1 (number of 20 students, good category 14 students with 70% presentation, quite good 5 students with 25% presentation, and very good category 1 student with 5% presentation). There was an increase in Cycle II with an increase in presentation of 35% in the very good category and a decrease in presentation of 10%. The conclusion is that the use of LKPD based on the make a match model can improve the digital writing skills of low grade elementary schools.